Restructuración comercial administrativa de la Distribuidora Jorge Mario Uribe G.-S.A., en la Agencia de Bogotá, D.C. (2019)
In the present work, an administrative commercial restructuring was carried out where the various tools of Industrial Engineering were used to diagnose and determine the appropriate strategies that help to improve the business and administrative processes of the organization. This restructuring was carried out by means of four chapters, the first was an external and internal diagnosis of the company where it was possible to identify the strengths, threats, weaknesses and opportunities of the organization, the second a market study where a respective analysis of the clients and the products managed by this agency was carried out in order to be able to establish a research of the administrative and thus to establish a third party feasibility.